ڈاکٹر یٰسین مظہر صدیقی کے افکار کی روشنی میں مغربی مصنفین کی نگارشات کا مطالعہ: An Examination of Western Authors’ Writings in the Light of Dr. Yasin Mazhar Siddiqui’s Thoughts. - Dr. Riffat Awais; Rimsha Khalid; Prof. Dr. Humayun Abbas (International Research Journal of Arabic and Islamic Studies, 2023)
It is a historical fact that since the beginning of Islam, Jews and Christians have had a negative attitude towards Islam. With the conquests of Islam, their prejudice and enmity increased, so they first targeted the personality of the Prophet of Islam, which originated with John Of Demuscus(700-779 AD). He started a movement against formal Islam and the Prophet of Islam by writing "Mahawarat al-Muslim" and "Irshadat al-Nasaari fi Jadal al-Muslimin" whose effects are seen in later periods as well. The famous contemporary biographer Dr. Muhammad Yasin Mazhar Siddiqui, who has introduced the new generation to the socio-economic aspects of the biography of Tayyaba, on the one hand, and on the other hand, has also provided awareness about the biographies of Western writers.The movement is divided into the following two periods:1st - From the eighth century AD to the sixteenth century AD and 2nd -From the sixteenth century AD to the twentieth century AD. Dr. Siddiqui has described the details under the headings of introduction of western writers of these periods, review of their contents and criticism on them. This suggests that while Western scholars (non-Muslims) have adopted a negative attitude towards the Holy Prophet (PBUH), at some places they have also expressed moderate and balanced sentiments of goodwill. Through his study, the methods and styles of Western writers' books can also be traced. Rakmah has tried to fill this gap in this paper and has presented a review of these books.